Refraction of Light on Prisma Applications - Ni Luh Putri Setyaningsih; Gede Yohanes Arygunartha (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2022)
A prism is a clear object made of glass. Its uses include directing light beams, changing and invertingshadows, and breaking white light into the colors of the spectrum (rainbow colors). The difference in thecolor of the spectrum is caused by the difference in the wavelength and frequency of the constituent rays,so that in the medium these rays have different refractive indices. Assume that the medium around the prismis air. This is called the angle of deviation. The angle of deviation is the angle formed by the intersectionof the extended incident light and the extended refracted light leaving the prism. The light beam that comesto the prism in the direction of ED will be refracted along the line DF and so on out of the prism in thedirection of FG. It is difficult for us to see or mark the red spectrum and the purple spectrum due to theinfluence of light from outside the laboratory, so we need a dark enough room to see the spectrum. Difficultyin determining the direction of the light source so that it coincides with a predetermined normal line, thelight is out of focus (a bit wide).